ANALYSIS OF STUDENTS’ MISTAKES IN SOLVING MATH WORD PROBLEMS ON FRACTION IN THIRD GRADE OF SD NEGERI 1 TAMANWINANGUN IN ACADEMIC YEAR OF 2019/2020. - Desy Widya Astuti; Tri Saptuti Susiani; Wahyudi Wahyudi (Universitas Sebelas Maret, 2020)
The aims of the study were to analyze types, causes, and solutions to overcome students' mistakes in solving word problem on fraction. It was a qualitative research with a case study approach. Data collection techniques included documents, observation, written test, and interview. Data collection tools were word problems worksheets, interview guideline, and observation papers. The subjects were 10 out of 25 third grade students of SD Negeri 1 Tamanwinangun. The results showed that: (1) the types of students' mistakes were 30.7% of reading error, 40% of comprehension error, 6.5% of transformation error, 33.3% of process skill error, and 12% of encoding error; (2) the causes were internal factors coming from the students and the external factors coming from the teacher; (3) the solutions were to get the students write the statement and the question, to use effective learning strategies, and to push the students solve word problem by the proper procedure.